Marfans Syndrome with Dissecting Aortic Aneurysm - A Case Report - Rahaman, Mohammad Ferdous Ur; Chowdhury, Mohammad Mainul Hasan; Haque, Reehum; Paul, Nandita; Siddique, Md Abu; Banerjee, Sajal Krishna; Rahman, Mahbubur (University Heart Journal, 2015)
Marfans Syndrome patients with aortic root aneurysm or dissection may present with shortness of breath and chest pain and may be missed during clinical evaluation. Subsequently, sudden aortic rupture may occur in these groups of patients and give rise to fatal outcome. Increasing awareness of Marfanoid signs amongst clinicians are important for early diagnosis and treatment of dissecting aortic aneurysm. Marfans Syndrome with dissecting aortic aneurysm should not be overlooked among patients with shortness of breath, chest pain and aortic regurgitation. Here we report a case of Marfans Syndrome who presented with non-exertional chest pain. University Heart Journal Vol. 10, No. 1, January 2014; 39-41